Themes in official discourses on terrorism in Central Asia - Horsman, Stuart (2005)
This article explores the manner in which the governments of Central Asia, in particular Uzbekistan, have analysed and portrayed the actual and perceived threat from Islamist terrorism. It examines and critiques the core themes in this discourse, including the theoretical and legal definitions of the term terrorism, the delegitimisation and depoliticisation of the terrorist and the continuation of Soviet rhetoric on terrorism. It seeks to place this discourse in the wider political culture and objectives of the regimes and the broader security considerations of these newly independent states seeking to consolidate state and nationhood. - Reproduced.
Keywords: Terrorism - Central Asia; Terrorism